Combined use of rheology and portable low-field NMR in cystic fibrosis patients - Abrami, Michela; Maschio, Massimo; Conese, Massimo; Confalonieri, Marco; Gerin, Fabio; Dapas, Barbara; Farra, Rossella; Adrover, Alessandra; Torelli, Lucio; Ruaro, Barbara; Grassi, Gabriele; Grassi, Mario (Respiratory medicine, 2021)
As most cystic fibrosis (CF) patients progress to respiratory failure, lung functionality assessment is pivotal. We previously developed a test that indirectly monitors airways (inflammation/functional test) by measuring the spin-spin relaxation time (T2m) of the water hydrogens present in CF sputum. Here the T2m significance in the monitoring of CF lung disease was further investigated by studying the correlation of T2m with: 1) sputum viscoelasticity, 2) mucociliary clearability index (MCI)/cough clearability index (CCI) and 3) sputum average mesh-size. Sputum samples from 25 consenting CF subjects were analyzed by rheology tests (elastic modulus G and zero shear viscosity η0) and Low Field Nuclear Magnetic (LF-NMR) resonance (T2m). MCI/CCI were calculated from the rheological parameters. The average mesh-size (ξ) of the sputum structure was then evaluated by rheology/LF-NMR, together with FEV1 for each patient. There was an inverse correlation between G and η0 versus T2m, indicating that a worsening of the lung condition (T2m-FEV1 drop) is paralleled by an increase in sputum viscoelasticity (G and η0) favoring mucus stasis/inflammation. A direct correlation was also observed between T2m and MCI/CCI, showing that T2m provides information as to airway mucus clearing. Moreover, there was a direct correlation between T2m and the average sputum mesh size (ξ). We demonstrated a correlation between T2m (measured in CF patient's sputum) and the sputum viscoelasticity/average mesh-size and with MCI/CCI, parameters related to airway mucus clearing. Thus, the present data strengthen the potential of our test to provide indirect monitoring of airway disease course in CF patients as T2m depends on mucus solid concentration and nanostructure.